IDENTIFIKASI POLA PERJALANAN DAN PEMODELAN FREIGHT TRIP GENERATION KOMODITAS TEKSTIL STUDI KASUS: PUSAT PERDAGANGAN TANAH ABANG, JAKARTA - Khairu , Derrell Shaka; Nahry, Nahry; Gani, Adil Afrizal; Adwitiya, R Ivan (Prodi Teknik Sipil, Fakultas Teknik, Universitas Jember dan Forum Studi Transportasi antar Perguruan Tinggi, 2024)
The population and economy continue to grow, as does logistic activity, as the demand for goods depends on their mutual growth. The increasing demand for goods leads to more transportation, which results in congestion and pollution. This study analyzes travel patterns and freight trip generation in Tanah Abang Trade Center. In this regard, the author identifies the characteristics of freight transportation and models the generation of freight transportation trips produced and attracted by each store. Modelling is done through linear regression analysis to determine the best model among all the formed models. The results of the linear regression produce four models that can be considered